Obstacles to the Implementation of an Integrated National Alcohol Policy in Ireland: Nannies, Neo-Liberals and Joined-Up Government - BUTLER, SHANE (Cambridge University Press, 2009)
This article explores how proponents of a public health model of alcohol policy have, for more than a quarter of a century, argued consistently but unsuccessfully for an integrated national alcohol policy in the Republic of Ireland. It looks in particular at the past decade, a time when increases in alcohol consumption and related problems strengthened the case for such an integrated policy, and when managerial innovations in the sphere of cross-cutting management appeared to provide a template for its implementation. A number of explanations are offered for the refusal of successive governments to respond to what its advocates see as the only rational, evidence-based approach to the prevention of alcohol problems. It is argued that, unlike the Nordic countries, the political culture of independent Ireland has never been one in which the state could unilaterally impose strict alcohol control policies as a feature of its broader vision of the welfare state. It is also argued that during the recent period of economic prosperity (the so-called `Celtic Tiger? era) the country was characterised by a neo-liberal policy climate, which was specifically antipathetic to the idea that the state should interfere directly in the alcohol market with a view to preventing related problems. It is suggested that the social partnership model of governance, to which many people attributed the country's economic success, created an atmosphere of consensualism within which the state as mediator between the two main protagonists (the public health lobby and the drinks industry) was unwilling to challenge the drinks industry. It is also concluded that this failure to create a national alcohol policy based on public health principles demonstrates the limitations of the cross-cutting, or `joined-up?, approach to public management in those areas of social policy characterised by clashing value systems or fundamental conflicts of economic interest. Finally, it is acknowledged that in Ireland, as elsewhere, neo-liberal certitudes have been effectively dethroned by the economic recession and banking crisis of late 2008; whether these more straitened economic circumstances will provide a better fit for the `nanny state? ideals of the public health perspective on alcohol remains to be seen.
PUBLISHED
Keywords: Social Policy; Alcohol